Pemaknaan Ruang pada Masjid Kubah Emas: Kajian Semiotik Ruang - Zaman, Saefu (UI Scholars Hub, 2017)
Golden Dome Mosque is located in Depok City. Gold plating on its dome is the hallmark of this mosque. The purpose of building this mosque is as a symbol of Islamic glory in Indonesia. The purpose of this study is to describe how these meanings are built on the Golden Dome Mosque, both from mosque constructors and from people around the mosque. The method the writer uses is analysis of Danesi and Perron about cultural marks, known as three-dimensional analysis which includes temporal, notational, and structural analysis. The result of this research shows that the mosque creators and the people make the meaning of this mosque in its thirdness level, which is annotative in the notational dimension, analogical in structural dimension and dynamic in the temporal dimension. The conclusion of this research is the meaning of a cultural sign is on its thirdness level where it is based on individual free interpretations.